Picturing Arizona : The Photographic Record of the 1930s - Jensen, Kirsten M., 1969-; Morrissey, Katherine G. (Book collections on Project MUSE., 2005)
The more than one hundred images--by well-known photographers such as Dorothea Lange and Laura Gilpin as well as by an array of less familiar ones--places the work of local Arizonans alongside that of federal photographers both to illuminate the impact of the Depression on the state's distinctive racial and natural landscapes and to show the influence of differing cultural agendas on the photographic record. Includes essays by a variety of authors on life in 1930s Arizona and the photographers who documented it.